Odpowiedzi

2010-04-13T16:20:12+02:00
A - 3x=2x-10
-3x-2x=-10
-5x=-10
x=2

3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

b 2x-2=7-x
3x=9
c=3

(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=20
x=-4

c 10=4-2x
4-2x=10
-2x=10-4
-2x=6
x=-3

d -(2x-1) =4
-2x+1=4
-2x=6
x=-3

e 2(x+1)=x
2x+2=x
x=-2

f 2t-(3t+1)=6
2t-3t-1=6
-t=7
t=-7

g -(4+x)=2(3-x)
-4-x=6-2x
x=10

2010-04-13T16:42:18+02:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10 /:(-5)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9 /:3
x=3

(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x-17=3
-5x=20 /:(-5)
x=-4

c)10=4-2x
-2x=4-10
-2x=-6 /:(-2)
x=3

d)
-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 /:(-2)
x=1,5

e)
2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f)
2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7 /*(-)
t=-7

g)
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y+18=2y+18
2y-2y=18-18
0=0